ANALISIS STRATEGI PENGEMBANGAN BENTENG MAKES SEBAGAI OBYEK WISATA BUDAYA DI KABUPATEN BELU - Juita Lubrina Domina Bessie; Yuliana Olandina Soares (Universitas Nusa Cendana, 2021)
This study aims to analyze the development strategy of Cultural Tourism Object Benteng Makes in Belu Regency. The samples were 30 respondents who gained by using purposive sampling technique. Data analysis using SWOT. The results showed that based on Grand Strategy Matrix, the Cultural Tourism Object of Benteng Makes is in quadrant I which means it supports the strategy aggressively and also the strategy of SO (Strength Opportunities) as a priority strategy. The development strategy for Benteng Makes as a Cultural Tourism Object needs to be considered from various aspects of development such as tourists, adequate accessibility, attractions or tourism objects, service facilities around tourist objects, information and promotion as well as institutions in terms of quality human resources. Suggestions in this research are the need to provide facilities at the Cultural Tourism Object of Benteng Makes which is still lacking, the cooperation with related parties in order to maintain and preserve tourism objects, promote tourism objects to be better known and visited, as well as synergy with the Regional Government and Academics in terms of providing quality human resources in the tourism sector. Keywords: Development Strategy, Cultural Tourism, SWOT